Usual Care for Rural Veterans With Posttraumatic Stress Disorder. Issue 3 (23rd January 2017) - Grubbs, Kathleen M.; Fortney, John C.; Kimbrell, Tim; Pyne, Jeffrey M.; Hudson, Teresa; Robinson, Dean; Moore, William Mark; Custer, Paul; Schneider, Ronald; Schnurr, Paula P.
Abstract: Purpose: Community‐Based Outpatient Clinics (CBOCs) provide primary‐care‐based mental health services to rural veterans who live long distances from Veterans Affairs (VA) hospitals. Characterizing the composition of usual care will highlight the need and potential strategies to improve access to and engagement in evidence‐based psychotherapy for posttraumatic stress disorder (PTSD). Method: Veterans (N = 132) with PTSD recruited from 5 large‐ (5, 000‐10, 000 patients) and 6 medium‐sized (1, 500‐4, 999) CBOCs were enrolled in the usual care arm of a randomized control trial for a PTSD collaborative care study. Chart review procedures classified all mental health encounters during the 1‐year study period into 10 mutually exclusive categories (7 psychotherapy and 3 medication management). Findings: Seventy‐two percent of participants received at least 1 medication management encounter with 30% of encounters being delivered via interactive video. More than half of veterans (58.3%) received at least 1 session of psychotherapy. Only 12.1% received a session of therapy classified as an evidence‐based psychotherapy for PTSD. The vast majority of psychotherapy encounters were delivered in group format and only a small proportion were delivered via interactive video. Conclusions: Findings suggest that veterans diagnosed with PTSD who receive their mental health treatment in large and medium CBOCs are likely to receive medication management, and very few veterans received evidence‐based psychotherapy. There may be ways to increase access to evidence‐based psychotherapy by expanding the use of interactive video to connect specialty mental health providers with patients, hosted either in CBOCs or in home‐based care, and to offer more group‐based therapies.